2011
DOI: 10.1245/s10434-011-1814-0
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Neutrophil-to-Lymphocyte Ratio in Predicting Short- and Long-Term Mortality in Breast Cancer Patients

Abstract: NLR is an independent predictor of short- and long-term mortality in breast cancer patients with NLR > 3.3. We suggest prospective studies to evaluate the NLR as a simple prognostic test for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
416
7
16

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(449 citation statements)
references
References 24 publications
10
416
7
16
Order By: Relevance
“…In this study we found that 57 Several studies reported the relationship between increased NLR and worse prognostic outcomes in various cancers including breast, colorectal and hepatocellular carcinomas, as well as, several urinary malignancies including prostate, bladder and renal cell carcinomas (RCC). [9][10][11][12][13][14] Proctor et al [15] performed a Scottish Cancer Registry review across 11 different malignancies, including 8759 patients, and noted a significantly increased risk of cancer-specific (HR=1.76) and overall mortality (HR=1.77) in patients with a preoperative NLR>5. Our results could not demonstrate the presence of any significant relationship between the NLR and PFS or CSS.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we found that 57 Several studies reported the relationship between increased NLR and worse prognostic outcomes in various cancers including breast, colorectal and hepatocellular carcinomas, as well as, several urinary malignancies including prostate, bladder and renal cell carcinomas (RCC). [9][10][11][12][13][14] Proctor et al [15] performed a Scottish Cancer Registry review across 11 different malignancies, including 8759 patients, and noted a significantly increased risk of cancer-specific (HR=1.76) and overall mortality (HR=1.77) in patients with a preoperative NLR>5. Our results could not demonstrate the presence of any significant relationship between the NLR and PFS or CSS.…”
Section: Discussionmentioning
confidence: 99%
“…After that, emerging evidences from several studies have pointed out that NLR has a prognostic value in patients with pancreatic (Aliustaoglu et al, 2010), breast (Azab et al, 2012), lung (Kaya et al, 2013;Unal et al, 2013) and gastric (Jung et al, 2011) cancers. Recent literature has relatively fewer papers that focused on the significance of the pre-treatment NLR in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Larger platelets are more metabolically and enzymatically active than smaller platelets (Mangalpally et al, 2010). Recently, elevated preoperative or pretreatment NLR, PLR and MPV detected in peripheral blood have been identified in various cancers, including colon cancer, esophageal cancer, gastric cancer ovarian cancer and breast cancer (Walsh et al, 2005;Gwak et al, 2007;Smith et al, 2009;Sharaiha et al, 2011;Thavaramara et al, 2011;Azab et al, 2012;Kilincalp et al 2013).…”
Section: Introductionmentioning
confidence: 99%